Diffusion of Particles on a Fluctuating Surface - Alexander Tarasenko; Lubomir Jastrabik (Adsorption Science & Technology)
Using kinetic Monte Carlo simulations, we have investigated within the framework of a simple lattice–gas diffusion model, the diffusion of particles adsorbed onto a lattice with moving surface atoms. Dynamic surface reconstruction was found to substantially increase the particle diffusion coefficient and change the activation energy.